Implementation of Child-Centered Learning to Increase Independence in the PKK Gemilang Tamansatriyan Playgroup - Iis Nurul Komariyah; Siti Muntomimah (Bulletin of Early Childhood, 2024)
Child-centered learning is unique in contributing to early childhood independence. The implementation of child-centered learning requires extra attention from the teacher's side, but from the student's side, it requires focused attention that allows for the absence of teachers in activities. This qualitative descriptive study, which lasted for one year, explained the important role of teachers and parents in the process of early childhood independence using a centered learning approach. The research results show that the role of teachers in the process of increasing children's independence in learning requires a fairly high level of teacher innovation and sensitivity in the process of implementing centered learning. Teachers still need a considerable amount of time to build early childhood independence comprehensively. Starting from sensitivity to students, learning innovation in centers, and communication with parents. Teachers understand the importance of early childhood independence learning will greatly influence the character of early childhood in the future. Teachers' hard work in unique centered learning innovations must be appreciated because it has many complex functions and benefits for early childhood development